Nutritional level, health, and subjective well-being in elderly - Martins, Emília (2022)
Literature points out the positive association between food, good health, and life satisfaction, manly in elderly. The purpose of this ex post facto quantitative study was to analyse the relationship between nutrition level, health, and subjective well-being, also exploring sociodemographic variables, in a convenience sample of 550 community-dwelling elderly. Participants were between 63 and 94 (72,85+6,56) years-old, mostly female (69,3%), from the inland (79,2%), living accompanied (62,2%) and in rural areas (67,9%). A sociodemographic questionnaire, Mini-Nutritional Assessment, Satisfaction With Life Scale, and Positive and Negative Affect Scales were used in data collection. Data analysis was performed in SPSS 27, assuming a 95% confidence level. Nutritional level was positively correlated with life satisfaction (r,- ,165, p= ,004) and inverse associated with negative affect (r,- -,308, p<,00l). Those who showed a very bad self-perception of health, were older and lived alone, presented lower nutritional levels (p<,05). Participants with health problems showed higher levels of negative affect (p<,001). Elderly with better health self-perception presented higher results in life satisfaction - (•,-271 , p<,001) and positive affect (r,-244, p<,001), contrary to those with worst self-perception of health, who were older (r,- -, 178, p<,001), with higher BMI (r,- - 173, p<,001) and also higher scores in negative affect (r,- -,217, p<,001). The results in our sample confirmed the previous relationship between the variables studied. It emphasizes the assessment of nutritional status and health education, as well as creating policies to promote the practice of physical activity in cities.